DEVELOPING A NEW ENCRYPTION TECHNOLOGY USING RECONFIGURABLE MULTI-VALUED LOGIC OPERATORS - Michael A. Smith (Academic Reseach Library for International Journal of Computer Science & Information System, 2025)
This paper presents a real option approach to the valuation of the default risk of residential mortgages. Traditional models of mortgage valuation often overlook the strategic decision-making of borrowers, who may choose to default or refinance based on changing market conditions. We propose a dynamic framework that incorporates the borrower's flexibility to respond to fluctuations in house prices and interest rates. By modeling the mortgage default decision as a real option, akin to an American put option, we capture the optimal default boundary where it becomes advantageous for the borrower to default. Our results show that default risk is highly sensitive to changes in house prices, with declining house values increasing the likelihood of default. Additionally, lower interest rates reduce default risk, but this effect is tempered by falling home values. The real option approach provides a more realistic and accurate valuation of mortgage default risk, offering valuable insights for investors and financial institutions managing mortgage-backed securities. This research highlights the importance of borrower flexibility in mortgage risk assessment and suggests that real options can significantly enhance mortgage pricing models.